Research on Function-Interface Design of Old and Antique Hongmu Furniture E-commerce Platform in the Second-hand Economy Environment - Science Author (UNC Test Journal, 2025)
Abstract goes here.
Keywords: E-commerce platform; Old and antique hongmu furniture; Analytic hierarchy process